Analysis of Changes in the Sound of Arabic Loan Words in the Translation of Akidatul Awam by Syekh Ahmad Marzuki (Crowley's Theory Perspective) - Wemamah, A-esah; Aulia, Fahnida (UIN ANTASARI, 2023)
Arabic has considerable influence over the Indonesian language, namely in vocabulary or loan words. This study aims to identify various forms of sound changes that occur in loanwords in the translation of the text Akidatul Awam. Using qualitative descriptive analysis, the researcher examined the data to discern the Arabic loan words in the text that take on an Indonesian phoneme. The results found 80 borrowed words in the translation of Akidatul Awam with various forms of sound changes in Crowley's theory; namely sound attenuation, sound reinforcement and sound addition. This research is expected to be able to increase knowledge in the field of linguistics, and assist language users in choosing and distinguishing loan words that are standard in Indonesian.